2020
DOI: 10.1080/21655979.2020.1823729
|View full text |Cite
|
Sign up to set email alerts
|

Silencing cyclophilin A improves insulin secretion, reduces cell apoptosis, and alleviates inflammation as well as oxidant stress in high glucose-induced pancreatic β-cells via MAPK/NF-kb signaling pathway

Abstract: (2020) Silencing cyclophilin A improves insulin secretion, reduces cell apoptosis, and alleviates inflammation as well as oxidant stress in high glucose-induced pancreatic β-cells via MAPK/NF-kb signaling pathway,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Therefore, we designed a study on the direct effect of empagliflozin on pancreatic β cells in vitro . Pancreatic β cells attacked by high glucose are a common diabetic cell model since insulin deficiency caused by pancreatic β cells dysfunction is an important pathogenic factor of diabetes mellitus [ 27 , 43 , 44 ]. Consistent with previous studies [ 45–47 ], using the CCK-8 assay, we found that the higher the concentration of glucose, the lower the activity of pancreatic β cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we designed a study on the direct effect of empagliflozin on pancreatic β cells in vitro . Pancreatic β cells attacked by high glucose are a common diabetic cell model since insulin deficiency caused by pancreatic β cells dysfunction is an important pathogenic factor of diabetes mellitus [ 27 , 43 , 44 ]. Consistent with previous studies [ 45–47 ], using the CCK-8 assay, we found that the higher the concentration of glucose, the lower the activity of pancreatic β cells.…”
Section: Discussionmentioning
confidence: 99%
“…High glucose group: complete culture medium with 6 g/L glucose; C. High glucose+EMPA group: cells were pretreated with 6 g/L high glucose complete medium for 2 h, and then an appropriate amount of empagliflozin was added at a concentration of 200 nmol/L in the complete medium. All the groups were processed for 24 h [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The signal pathways regulating the actions of CCL20 in breast cancer are diverse and complex, where the activation of a pathway signals several other downstream pathways. Besides the well-known functions of nuclear factor-kB (NF-kB) in regulating immune response and inflammation [ 105 , 106 ], increasing evidence supports their involvement in several oncogenic processes [ 105 , 107 ]. They are known to regulate the expression of proinflammatory genes, including those encoding chemokines and cytokines [ 106 ].…”
Section: Signal Pathways Regulating Ccl20 In Breast Cancermentioning
confidence: 99%
“…Inhibition of CyPA can promote insulin secretion, reduce the pancreatic β cell apoptosis caused by high glucose, and alleviate inflammation and oxidative stress. [10] CyPA is involved in inflammatory reactions, which is closely related to diabetes and atherosclerosis. [11] CyPA is also a newly identified RNA binding protein.…”
Section: Introductionmentioning
confidence: 99%